Estrutura em quilha Brasil central, uma feicao fundamental na geologia de Goias e Tocantins - Hasui, Y.; Costa, J. B S; Haralyi, N. L E (My University, 1994)
The older Precambrian geological setting of north Goias/south Tocantins includes three areas of granite-greenstone terrains formed of medium-grade gneisses with associated greenstone belts and nepheline syenitic gneisses, separated by two orogenic belts composing a crustal-scale pop-up structure. The movements were firstly oblique towards NW along the northwestern NNE-SSW-trending Porto Nacional suture, and afterwards of essentially frontal type towards ESE along the southeastern Ceres suture of curved geometry with N-S direction at north and WNW-ESE at the south. The Porangatu block, limited by these sutures, was upthrusted over the neighbouring underthrusted blocks. Three principal kinematic phases are recognized along the orogenic belts. -from English summary
The central Brasil pop-up structure, a fundamental structural feature of Goias and Tocantins
Keywords: orogenesis; pop up structure; Precambrian; tectonic evolution; Brazil, Goias; Brazil, Tocantins